Looking back, looking forward: Methodological challenges and future directions in research on persons with profound intellectual and multiple disabilities - Maes, Bea; Nijs, Sara; Vandesande, Sien; Van keer, Ines; Arthur‐Kelly, Michael; Dind, Juliane; Goldbart, Juliet; Petitpierre, Geneviève; Van der Putten, Annette (Journal of applied research in intellectual disabilities, 2021)
Background Within the context of the Special Interest Research Group (SIRG) on Persons with Profound Intellectual and Multiple Disabilities (PIMD), researchers often discuss the methodological problems and challenges they are confronted with. The aim of the current article was to give an overview of these challenges. Methods The challenges are centred on six topics. These reflect the main components of a study's design: (a) participant demarcation, (b) participant recruitment, (c) data collection and instruments, (d) data analysis, (e) ethics/including the “voice” of persons with PIMD and (f) theoretical models. Results Next, to describing the specific challenges, possible solutions and pathways to address them are discussed. These are illustrated by recent studies by the authors and other researchers in the field. Conclusions The current contribution wants to stimulate further discussion and exchange of ideas, and the development of creative research techniques.